Pengaruh Gaya Komunikasi Pustakawan Terhadap Minat Kunjung Pemustaka di Perpustakaan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Jariah, Jariah; Ramayanti, Rory (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT Introduction. This study aims to determine whether the librarian's communication style at the State Islamic University Library of Sulthan Thaha Saifuddin Jambi affects the interest of visiting visitors. This is based on the importance of communication which is a basic need of humans as social beings, and an important part of the library, especially in serving users. Data Collection Method. This study uses quantitative methods with data collection techniques used, namely questionnaires, observation, and documentation. The questionnaire in this study used a Likert scale. The population of this research is 8129 active students and the sample used is 99. The sample technique of this research uses incidental sampling technique. Data Analysis. The data analysis technique used descriptive data analysis with simple regression analysis techniques. To determine the presence or absence of influence in this study using hypothesis testing. Result and Discussion. The results of this study are the librarian's communication style variable obtained a score percentage of 78.29% which means that the influence of the librarian's communication style is in the very high category. The variable of visiting interest obtained a percentage score of 80.24%, which means that visiting interest is in the high category. Based on the results of the regression test, there is an influence between the librarian's communication style on visiting visitors' interest. This is shown by the linear regression equation Y = 6.510 + 0.808X and the t value of 8,985 and the significant value of 0.001. The regression results can be seen that the t value is 8,985 with a significant value of 0,000 <0.10, then Ho is rejected and Ha is accepted. Conclusions. Based on the research that has been done on the strong relationship between the librarian's communication style and visiting interest. With the librarian's communication style provided, it makes it easy for users to communicate with librarians to meet the information needs needed by the users.